Characterisation of zinc plant, cold-purification filter cake and leaching of indium by aqueous sulphuric acid solution - Sankum Nusen (2018)
© 2015 Chiang Mai University. All rights reserved. The filter cake, generated from the cold-purification stage in a zinc electrowinning plant and considered as a hazardous waste containing heavy metals, was characterized for its chemical and mineralogical compositions by inductively couple plasma-optical emission spectroscopy (ICP-OES), X-rays diffractometry (XRD) and scanning electron microscopyenergy dispersive X-rays spectrometry (SEM-EDS). Leaching of indium from the filter cake was consequently studied using aqueous sulphuric acid solution as leachant. Leaching parameters including temperature, time, solid-to-liquid ratio and stirring speed have been investigated and ICP-OES was used to determine the metal content in the leachate. Dissolution kinetics was studied using 1 M aqueous sulphuric acid solution, the temperature range of 40-80 °C, and the time up to 360 min, and it was found to be controlled mainly by diffusion through porous product following the spherical shrinking-core model. The optimum leaching temperature and time for indium is 40 °C and 90 min, respectively. The solid-to-liquid ratio higher than 1/4 g/ml is ineffective and the solid-to-liquid ratio of 1/12 g/ml was the optimum. Increasing the stirring speed over 700 rpm had little effects on indium dissolution, hence the stirring speed of 700 rpm was considered as the optimum. Copper and lead were hardly leached out by sulphuric acid solution. The results indicated that the cold-purification filter cake in the zinc electrowinning plant can be an intermediate source of indium, and that recovery of indium from this hazardous waste is important from the environmental point of view.